Comparative study of pomegranate and jacaranda seeds as functional components for the conjugated linolenic acid enrichment of yogurt. (August 2019) - Van Nieuwenhove, Carina P.; Moyano, Andrea; Castro-Gómez, Pilar; Fontecha, Javier; Sáez, Gabriel; Zárate, Gabriela; Pizarro, Patricia Luna
Abstract: Pomegranate (Punica granatum ) and jacaranda (Jacaranda mimosifolia ) seeds represent high natural sources of conjugated linolenic acids (CLnAs), predominantly as punicic and jacaric acid, respectively. Both CLnAs are known as potent anticarcinogenic compounds; however, they are poorly used in food development. We characterized pomegranate and jacaranda seeds (PS and JS, respectively) and seed oil and employed seed powder for the bioactive lipid enrichment of yogurt. The fibre and lipid contents were quite similar in PS and JS. The seed oil fatty acid (FA) profile was dominated by unsaturated fatty acids (∼87–89%), whereas the CLnA content varied from 31 to 69% (for JS and PS, respectively). A higher scavenging activity and phenolic content was determined for PS compared with JS oil. Compared to the control, yogurt enriched with 0.5% (w/v) PS or JS flour showed similar nutritional and pH values, but higher antioxidant activities, desirable FA and CLnA contents and lower atherogenicity indexes. Both bio-fortified yogurts showed high overall acceptability. For the first time, the feasibility of producing CLnA-enriched dairy foods using non-conventional plant seeds or waste seeds was performed, and these results encourage further studies on their functional effects for consumers. Highlights: Pomegranate and jacaranda seeds are rich sources of conjugated fatty acids. Conjugated linolenic acid isomer contents varied among seeds. Seeds were included as a functional ingredient for yogurt manufacture. Bioenriched yogurts showed high overall acceptability and a healthier fatty acid profile.